STRATEGI PENINGKATKAN PENGHASILAN DRIVER OJEK ONLINE DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI DITINJAU DARI PERSPEKTIF EKONOMI ISLAM (Studi Kasus Pada Kelompok Pribumi GRAB Majenang di Kecamatan Majenang) - Fajar Hasani; Haqibul Mujib (Syari'ah Economics, 2019)
This study aims to find out what strategies are being used to increase the income of Grab Majenang drivers. Then the researchers will dig up information on how to improve the economic welfare of drivers after becoming a Grab driver. After that, the researcher then examined the strategies developed and implemented by the drivers of the Grab Majenang indigenous group based on an Islamic perspective. Data were collected by observation, interviews (interviews), and documentation. The analysis used is descriptive qualitative method, namely by formulating the data obtained and then classified in order to answer the formulation of the problem. The results of the study show that the strategies applied by drivers to increase income in an effort to improve their economic welfare have been good and appropriate to be applied both in the short and long term. Then the changes in the economic welfare of the drivers, namely from before becoming a Grab driver (partner) and after becoming a Grab driver (partner), the results are quite drastic in improving their economy. Furthermore, it is obtained from the results of reviewing and analyzing these strategies using guidelines that are in accordance with the Islamic economic perspective. So that the results of an Islamic economic view on these strategies show that these strategies are feasible and good to implement because they do not contain elements of fraud or fraud that can harm other parties which is strictly prohibited by Islam.